Interplay of weak interactions in the atom-by-atom condensation of xenon within quantum boxes - Nowakowska, Sylwia; Gade, Lutz H. (Nature Communications, 2015)
Condensation in the regime of weakly interactions is of fundamental importance. Here, the authors study the condensation process one atom at a time, showing the forces driving the behaviour of xenon atoms as they condense into aggregate structures in nanoscale pores.